(untitled) (Research, Society and Development, 2021)
This article is a descriptive study, of the integrative literature review type, with a qualitative character. From the publications found, cases in which there was self-care and in which the patient received assistance were analyzed. In situations where the patient was not followed up and promoted self-care, a higher rate of anxiety was noted, which suffered a significant reduction with follow-up, promoting greater well-being of users. (Krouse, 2016). In self-care, it is possible to observe that there are external factors that influence the quality of life, that is, there are factors that facilitate or hinder this condition. A study in Northern California, Oregon and Washington, carried out by Bulkley, J. E, et al , who sent a survey to 177 patients with 5 years of ostomy or more. Of these, 66% responded, of which 63% reported at least one difficulty in promoting self-care. The most reported problems were the frequency of bag exchange, leaks and local dermal complications. Thus, the promotion of self-care scores points for the perfect recovery and monitoring of those in the ostomy scenario. It is noteworthy that being ostomized implies changes in the lifestyle. Whether in the role of a multidisciplinary team or in the training of the family group, the current study observed the need for updating and the search process for a better adaptation to the patient’s life.